RTMS of the superior parietal lobule improves contrast discrimination but has no effect on the perception of distance between stimuli in the image plane. (October 2022) - Biagi, Nicolo; Goodwin, Charlotte; Field, David T.
The superior parietal lobule (SPL) is a region of the brain that has been associated with a diverse range of high-level visual and cognitive functions. This suggested the possibility that it supports a lower-level function that is engaged by a wide range of experimental tasks. Analysis of tasks used in previous studies suggests that one such lower-level function might be the perception of the distance between stimuli in the image plane. In this study, we applied online high-frequency repetitive transcranial magnetic stimulation (rTMS) over the left SPL or the vertex in order to further investigate the role played by this region in the perceived visual separation between points. As a control task, we asked participants to detect the difference in contrast between two Gabor patches. The results failed to support the main hypothesis, but we unexpectedly found that rTMS to left SPL improved peripheral contrast discrimination. Previous studies have found that rTMS to the right frontal eye field, which has strong functional connectivity with the SPL, has the same effect, suggesting the two areas work together to influence early visual areas.